2020
DOI: 10.1186/s13287-020-1570-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-135a derived from human amnion mesenchymal stem cells promotes cutaneous wound healing in rats and fibroblast migration by directly inhibiting LATS2 expression

Abstract: Background: Wound healing is a complex pathophysiological process that involves a variety of cells and cytokines. In this study, we found that local injection of human amnion mesenchymal stem cells into wounds in rats could promote wound healing. Therefore, we hypothesized that the exosomes of human amnion mesenchymal stem cells contain substances that regulate the migration of epidermal cells. It has been reported that miR-135a is involved in cell migration and transformation. However, there have been no repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 29 publications
0
33
0
3
Order By: Relevance
“…Therefore, it is generally believed that the paracrine effect of cells, rather than their differentiation, is the main underlying repair mechanism for stem cell-based therapy [39,40]. As such, several cell-free methods using the secretion of MSCs, such as their condition medium [41,42] or exosomes [43,44], have been introduced to treat skin wounds. Chen et al demonstrated that exosomes derived from human USCs can effectively improve skin cell functions in vitro and obviously enhanced wound healing in diabetic mice [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is generally believed that the paracrine effect of cells, rather than their differentiation, is the main underlying repair mechanism for stem cell-based therapy [39,40]. As such, several cell-free methods using the secretion of MSCs, such as their condition medium [41,42] or exosomes [43,44], have been introduced to treat skin wounds. Chen et al demonstrated that exosomes derived from human USCs can effectively improve skin cell functions in vitro and obviously enhanced wound healing in diabetic mice [8].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that hAMSCs and hAMSCs-CM efficiently cured heat stress-induced skin injury by inhibiting apoptosis and promoting proliferation of skin cells through activating PI3K/Akt signaling pathway [ 24 ]. Gao et al observed that the exosome-derived miR-135a from hAMSCs promoted cutaneous wound healing and fibroblast migration by downregulating LATS2 levels [ 169 ]. A combined administration of hAMSCs/Matriderm was beneficial to potentiate the therapeutic effects of hAMSCs on wound healing [ 170 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Besides, the significance of AdMSC-EVs cargo MALAT1 (metastasis-associated lung adenocarcinoma transcript 1, a long non-coding RNA) in maintaining fibroblast migration to wound sites was proved since EVs lacking MALAT1 decreased fibroblast migration rate by halving. Other authors determined that fibroblast migration is supported through downregulation of LATS2 (large tumour suppressor 2) levels by miR-135 transferred by human amnion MSC-EVs [ 156 ].…”
Section: Stem Cell-derived Extracellular Vesicles In Skin Wound Healingmentioning
confidence: 99%